Structural analyses of self-centring-beam moment-frames under near-fault and far-field earthquakes. Issue 145 (June 2021) - Huang, Xiaogang; Zhou, Zhen; Wang, Yuhang; Yang, Lin; Wang, Yupei
Abstract: A self-centring-beam (SCB) is a new structural member with a capacity for recentring and deformation compatibility for moment-frames (MFs). This paper examines the lateral drift responses of SCB-MFs when subjected to the far-field (FF) record set, near-field pulse (NF) record set, and near-field no pulse (NP) record set. A series of 3-, 6-, 9-, and 12-storey SCB-MFs were modelled and analysed using centralized spring models in OpenSees software. Based on the observed differences in the experiments, a parametric analysis of the effect of the three design factors was conducted. The three design factors were initial stiffness, gap-opening moment, and maximum self-centring rotation at the beam ends. The analyses indicated that all of the SCB-MFs, except for 3-storey SCB-MFs, experienced an obvious increase in the inter-storey drift demand as the excitation was changed from the FF and NP to the NF records. Highlights: Structural analyses of different storey SCB-MFs were performed under near-fault and far-field earthquakes. The roof displacement time histories of SCB-MFs were presented to explore the influence of obvious velocity pulses and acceleration spectra. The effects of initial stiffnesses, gap-opening moments, and maximum self-centring limits on the maximum drift responses of self-centring frames were investigated.